What is a Mode? Smell, Olfactory Perception, and the Notion of Mode in Multimodal Mediated Theory - Norris, Sigrid (Multimodal Research Centre, 2013)
Moving towards multimodal mediated theory, I propose to define a mode as a system of mediated action that comes about through concrete lower-level actions that social actors take in the world. In order to explain exactly how a mode is a system of mediated action, I turn to a perfume blog and use one blog entry as my starting point. The mode that I primarily focus on in this article is the mode of smell, explicating that the mode of smell is not synonymous with olfactory perception, even though modal development of smell is certainly partially dependent upon olfactory perception. As I am ostensibly focusing on the one mode, I once again problematize this notion of countability and delineate the purely theoretical and heuristic unit of mode (Norris, 2004). I clarify that modes a) do not exist in the world as they are purely theoretical in nature; b) that modes can be delineated in various ways; and c) that modes are never singular. Even though the concept of mode is problematical – and in my view needs to always be problematized – I argue that the term and the notion of mode is theoretically useful as it allows us to talk about and better understand communication and (inter)action in three respects: 1. The notion of mode allows us to investigate regularities as residing on a continuum somewhere between the social actor(s) and the mediational means; 2. The theoretical notion of mode embraces socio-cultural and historical as well as individual characteristics, never prioritising any of these and always embracing the tension that exists between social actor(s) and mediational means; and 3. The theoretical notion of mode demonstrates that modal development through concrete lower-level actions taken in the world, is transferable to other lower-level actions taken.
Keywords: Mode; Multimodality; Olfactory perception; Smell; Systems of mediated action